Case Report: Relapsing systemic lupus erythematosus treated with dual rituximab and anifrolumab therapy - Lee, Sunnie; Choi, Janet; Benitez, Steven; Lee, Jeanie (Frontiers in Medicine, 2026)
While biologic monotherapy is commonly used in the management of moderate-to-severe systemic lupus erythematosus (SLE), limited data exists regarding the efficacy and safety of dual biologic therapy in SLE. We report the case of a 42-year-old woman with a history of SLE complicated by Rowell Syndrome (RS) that was managed on anifrolumab and a recent diagnosis of moyamoya disease, who presented with new-onset lower extremity weakness. Laboratory testing was notable for active lupus serologies, and magnetic resonance angiography (MRA) findings were consistent with worsening moyamoya syndrome. Given the clinical and radiographic findings, a diagnosis of CNS lupus was suspected. Anifrolumab was discontinued and she was started on pulse dose corticosteroids and rituximab, resulting in marked neurologic improvement. However, she subsequently experienced a flare of RS. Anifrolumab was reintroduced while she remained on rituximab, leading to significant clinical improvement of her cutaneous symptoms. To our knowledge, we present the first case of successful treatment of refractory SLE with both cutaneous and neurologic involvement utilizing dual biologic therapy with rituximab and anifrolumab.